Dynamically responsive intervention for tremor suppression. - Manto, M.
The DRIFTS (Dynamically Responsive Intervention For Tremor Suppression) project aims to create wearable active orthoses that suppress upper-limb tremor while allowing natural movement. We present an overview this multidisciplinary project. This project is financially supported by the European Commission's Fifth Framework Programme and aims to create proof-of-concept prototypes of wearable active orthoses for the suppression of upper limb tremor while preserving natural movement. Another major goal of the project is the development of a prototyping and evaluation platform for the future elaboration of wearable ambulatory tremor suppression devices. The prototyping platform will be used to assess the efficacy of available sensing, actuating, and control technologies for tremor suppression.
Keywords: DRIFTS project; Dynamically Responsive Intervention For Tremor Suppression; Actuating technologies; Control technologies; Dynamically responsive intervention; Multidisciplinary project; Natural movement preservation; Prototyping-evaluation platform; Sensing technologies; Upper-limb tremor suppression; Wearable ambulatory tremor suppression devices